1995
DOI: 10.1557/proc-418-397
|View full text |Cite
|
Sign up to set email alerts
|

Detonation in Shocked Homogeneous High Explosives

Abstract: We have studied shock-induced changes in homogeneous high explosives including nitromethane, tetranitromethane, and single crystals of pentaerythritol tetranitrate (PETN) by using fast time-resolved emission and Raman spectroscopy at a two-stage light-gas gun. The results reveal three distinct steps during which the homogeneous explosives chemically evolve to final detonation products. These are i) the initiation of shock compressed high explosives after an induction period, ii) thermal explosion of shock-comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The shortest-time temperatures we could reliably determine were 3510 ± 220 K for NM at 5 ns and 3470 ± 250 K at 3.5 ns for NM/EDA, so the temperatures were identical within experimental error. These values are quite close to the ∼3600 K values obtained by Yoo and co-workers, and by Bouyer and co-workers. , …”
Section: Resultssupporting
confidence: 91%
“…The shortest-time temperatures we could reliably determine were 3510 ± 220 K for NM at 5 ns and 3470 ± 250 K at 3.5 ns for NM/EDA, so the temperatures were identical within experimental error. These values are quite close to the ∼3600 K values obtained by Yoo and co-workers, and by Bouyer and co-workers. , …”
Section: Resultssupporting
confidence: 91%
“…This means that shocked NM is transparent and we will consider that its absorption coefficient is the same as that for neat NM. Besides, Yoo et al [22] pointed out that shocked NM remains transparent in the spectral range 0.35-0.75 µm. The radiant temperature after shock entrance, prior to the detonation transition, reaches 2500 K. Such a temperature is not in agreement with Chaiken model, which predicts a shock temperature of about 1000 K. It is also clearly greater than those predicted by Lysne and Hardesty [23] (1100-1200 K) or Winey and Gupta [24] (1000 K).…”
Section: Discussionmentioning
confidence: 99%
“…Kapila et al investigated the gaseous systems and found that the super detonation develops gradually by an initial weak detonation . Yoo et al classified the shock-induced chemical reaction processes in terms of three steps: First, an unreactive induction period This is followed by a shock initiated chemical reactions period This finally turns into a rapid exothermic reactions period …”
Section: Introductionmentioning
confidence: 99%